DISEASE PREVENTION AND CONTROL STRATEGIES IN THE ORPHANAGE OF BANGLADESH: AN ISLAMIC PERSPECTIVE - Md. Mahfuz Ashraf; Sheikh Mahmud Al-Azhari; Ishfaque Khilji; Mohammad Islam (International Islamic Medicine Forum, 2026)
This study examined the role of hygiene practices and lifestyle on the physical, mental, and spiritual well-being of orphaned students using a cross-sectional design. Most respondents were male with a mean age of 25.38±5.53 years, living in crowded conditions with limited sanitation facilities. Despite this, the majority demonstrated high adherence to Islamic hygiene practices, including personal hygiene, oral hygiene, and ablution, as well as sleep hygiene, despite limited routine physical activity. Respondents also reported benefits such as increased mental clarity, reduced stress, and improved mood. Furthermore, there was a significant association between hygiene practices and a decrease in healthcare visits. Overall, Islamic hygiene and lifestyle practices contribute to improved well-being and have the potential to shape healthier and more resilient individuals.